FEATURES OF THE STRUCTURE OF FOREST COVER ON THE EXAMPLE OF THE INTENSIVE LEVEL POLYGON “KIVACH” (REPUBLIC OF KARELIA) - S. A. Moshnikov; A. N. Pekkoev (Вопросы лесной науки, 2024)
The study represents the results of the forest inventory observations (the data of forest stand, undergrowth, understory, coarse woody debris) based on the reconnaissance stage (the express assessment) of the research on the intensive level polygon “Kivach” (Republic of Karelia) within the implementation of the monitoring framework of the carbon budget in the forests of Russian Federation. We found that within the polygon the old-growth overmature coniferous forest stands dominate: 71% of the test site area is represented by pine stands, 16% – by spruce ones. The blueberry forest type predominates representing 76 and 38% of pine and spruce stands, respectively. The productivity of the studied forest stands is middle: the average quality class of pine stands is II.7, whereas spruce and birch stands have III.0 only. The composition of the undergrowth is dominated by spruce with the average density in range from 0.14 to 1.70 thousand pcs ha-1. Pine undergrowth is most represented in lingonberry and blueberry pine forests. The understory layer is formed by tree species typical of coniferous boreal forests – common mountain ash, gray alder, goat willow, common juniper, and needle hips. Within the polygon the coarse woody debris amount varies widely and its distribution by stock, type (standing and downed deadwood and stumps) and species identity depends on the dominant tree species of the stand and forest site conditions. Despite the old-growth and low-disturbed status, the forest sites of the polygon “Kivach” largely reflect the tree species and typological diversity of the forests in the middle taiga subzone.